Strategi Pembelajaran Tahfidz al-Qur’an bagi Anak Berkebutuhan Khusus di Rumah Tahfidz Inspirasi IZI - Latifah Azzahara; Mustafa (Lembaga Yasin AlSys, 2026)
The assumption that children with special needs experience difficulties in memorizing the Qur’an remains prevalent, even though appropriate learning strategies can help them optimize their memorization potential. This study aims to describe Qur’an memorization learning strategies for children with special needs at Rumah Tahfidz Inspirasi IZI and to identify the strengths and limitations of the strategies implemented. The study employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation, involving teachers as key informants and the institution’s leader, facilitators, and students’ parents as supporting informants. The findings indicate that learning was conducted individually and flexibly and was centered on the needs of each student. Learning planning began with an initial assessment, while its implementation combined the talaqqi, wahdah, and takrir methods, supported by the SABAR approach, which consists of Smiling, Children as the center of learning, Simple language, Appreciation, and Routine. Evaluation was conducted through individual tasmi’ while considering the children’s comfort, emotional stability, and engagement during learning. The strengths of this strategy include the alignment of learning with the children’s characteristics, emotional closeness between teachers and students, the establishment of realistic memorization targets, the use of varied learning media, and improvements in the children’s motivation and self-confidence. Its limitations include the limited number of competent teachers, the need for longer learning periods, and the considerable demands for patience and energy. These findings affirm that adaptive, individualized, and collaborative learning strategies can support successful Qur’an memorization learning for children with special needs. This study contributes as a reference for developing more inclusive Qur’an memorization instruction in Islamic educational institutions.